Duration of Gadget Use and Severity of Dry Eye Syndrome based on the Ocular Surface Disease Index (OSDI) Questionnaire in Final-Year Students of the Faculty of Medicine, Universitas Airlangga - Subagiono, Arya Agung Hari; Komaratih, Evelyn; Umiastuti, Pirlina; Loebis, Rozalina (Universitas Airlangga, 2025)
Highlights: Screen time is one of the risk factors for dry eye disease (DED). Therefore, students are at high risk for DED. The ocular surface disease index (OSDI) is one method used to assess dry eye disease based on subjective symptoms. However, the correlation between screen time and the incidence of dry eye and/or its severity based on OSDI produces varying results. The majority of respondents had dry eyes based on OSDI. There was no correlation between screen time and dry eye incidence or severity based on OSDI parameters. Females had higher mean OSDI scores than males. Abstract Introduction: People’s screen time surged during and after the COVID-19 pandemic. Screen time was a risk factor for dry eye disease (DED). This study examined the correlation between screen time and DED severity based on an ocular surface disease index (OSDI) questionnaire in final-year undergraduate students of the Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia. Methods: This was a cross-sectional study. Respondents were recruited via a total sampling method. One hundred eight students participated in this study. Independent variables were sex, average duration of device use per day, and degree of daily gadget usage time. Dependent variables were OSDI score, degree of dry eye based on OSDI score, and dry eye incidence. Chi-Square, Spearman, Kruskal-Wallis, and Mann-Whitney tests were used in data analysis. Results: There was no significant relationship between daily gadget use duration and OSDI score (p=0.497; r=-0.066) and between the degree of daily gadget usage time and dry eye severity (p=0.609; r=0.050). Sex was unrelated to dry eye incidence (p=0.072) nor severity (p=0.125). There were no significant differences in daily gadget use duration between dry eye vs non-dry eye respondents (p=0.926) and across dry eye severity (p=0.934). There were no significant differences in OSDI scores between degrees of screen time (p=0.978). There was no significant correlation between the incidence of dry eye and the degree of daily gadget usage time (p=0.640). Female respondents had higher mean OSDI scores than males (p=0.009). Conclusion: Screen time was not related to the incidence and severity of dry eye based on OSDI. However, many respondents had dry eyes based on OSDI.